Los nematodos formadores de quistes de la patata en España - Martinez-Beringola, M.L.=700 1 Franco, J.; Paz, L.M.; Gutierrez, M.P.
(Es, En)
ilus., ref.
Keywords: GLOBODERA ROSTOCHIENSIS; GLOBODERA PALLIDA; PATOTIPOS; NEMATODA; PLAGAS; ESPAÑA; PATATA